Composite Behavior of Reinforced Concrete T-Beam with Composite Slab - Eissa, Mahmoud; Celikag, Murude (Springer Heidelberg, 2022)
This paper investigates the possible benefits and difficulties of using composite slabs, consisting of galvanized steel decks and in situ concrete, in reinforced concrete (RC) framed structures. Three different test arrangements were used. A four-point static test (quasi-test) has compared the flexural behavior of the proposed composite slab with traditional solid slab used with a RC beam under gravity load. The m-k values arrangement measures longitudinal shear to evaluate the composite action between the steel deck and the RC slab. The composite action between the RC beam and the composite slab has been examined by using a slip capacity test through four different cases. Results of the quasi-test, showed that both slabs had similar flexural behavior and capacity, while the proposed composite flange had higher total deflection but smaller crack widths than solid concrete flanges. The composite slab's m-k values were found acceptable compared to those in the literature. Longitudinal shear stress with a ductile mode of failure was observed in all specimens. In the slip capacity test, the concrete's shear forces were transferred by the concrete itself since the beam and slabs were monolithic, where no slip between the slabs and the beam was observed. Comparing the proposed composite slab with commonly known slabs (solid concrete one-way, two-way, joist, and flat slabs) emphasizes the proposed slab's ability to reduce the overall weight with the same load-carrying capacity, while speeding up the construction process.
Keywords: Composite slab; Static test; Shear bond; Slip capacity; Push-off test; Composite slab in reinforced concrete frame